Evaluating E-Banking Service Quality and Customer Satisfaction: A Systematic Review in the Context of Nepal - Ram Paudel; Rashmi Roka Chhetri; Laba Kumar Shrestha; Rajesh Paudel; Anita Pokhrel; Rumisha Aryal (Paspama Institute, 2025)
Nepal has recorded significant improvements in electronic banking (e-banking) in the past years, but there remains a situation of persisting limitations (in terms of infrastructure, digital literacy level and disparity), which tends to affect user satisfaction alongside service delivery. Despite the rise in the scholarly attention given to e-banking in Nepal, the current evidence remains fragmentary, as an incomplete picture exists of the way in which the dimension of service quality influence the experience of e-banking users in Nepal. The primary aim of this systematic review is to critically examine the influence of e-banking service quality on customer satisfaction in Nepalese commercial banks. The review seeks to consolidate fragmented empirical findings and provide a clear understanding of which service dimensions most significantly impact satisfaction. In total 40 peer reviewed empirical studies published between 1985 and 2025 that were selected for a review as per PRISMA guidelines. The five dimensions of SERVQUAL were utilized in being as thorough as possible, with thematic synthesis, but the results were complemented by emergent variables, also considered important to the Nepalese case. In this overview, reliability, responsiveness, and security assurance are outlined as the key dimensions that define the satisfaction of users. Digital trust, infrastructure adequacy, and digital literacy are additional variables, which are proposed as mediating. The underutilized constructs of tangibles and empathy came out as important to rural and first-time users. This study contextualizes and extends SERVQUAL for use in developing digital economies, offering theoretical refinements and actionable insights for Nepalese banks and policymakers to foster inclusive and customer-centric e-banking services.